Roussoella guttulata (Roussoellaceae, Pleosporales), a novel bambusicolous ascomycete from Thailand - Zhang, Jing-Yi; Phookamsak, Rungtiwa; Boonmee, Saranyaphat; Hyde, Kevin D.; Dai, Dong-Qin; Lu, Yong-Zhong (Phytotaxa, 2020)
Roussoella guttulata sp. nov. (Roussoellaceae) was found on bamboo culms collected in the northeast of Thailand. Roussoella guttulata differs from other species in having immersed, gregarious, black pseudoascostromata, single and central ostiole with periphyses, thin-walled peridium composed of cells of textura angularis to textura prismatica and yellowish brown ascospores. The multigene phylogenetic analysis shows that the new species forms a distinct lineage basal to R. hysterioides, R. japanensis, R. scabrispora and R. verrucispora. The new species is compared with closely related Roussoella species. A full description, color photo plates and a phylogenetic tree to show the placement of the new species are provided.